Atherogenic Burden and Insulin Resistance in Non-Obese Women with Polycystic Ovary Syndrome: A Comparative Study with Healthy Controls - Andaç, Burak; Navdar Başaran, Mehtap; Eren, Gözde Nur (The European Research Journal, 2026)
Objectives: Polycystic ovary syndrome (PCOS) is associated with elevated cardiovascular disease (CVD) risk due to metabolic derangements. Although obesity contributes to CVD, the independent contribution of PCOS remains controversial. This study aimed to compare insulin resistance (IR) and atherogenic lipid indices across body mass index (BMI) categories within PCOS, to evaluate the diagnostic performance of atherogenic indices between non-obese PCOS and healthy controls, and to derive exploratory, data-driven thresholds that may inform cardiovascular risk assessment in non-obese PCOS. Methods: This single-center case-control study enrolled 65 treatment-naïve women newly diagnosed with PCOS (Rotterdam criteria 2003) and 100 age-matched healthy controls. A panel of IR and composite atherogenic lipid indices (e.g., Lipid Accumulation Product [LAP], Visceral Adiposity Index [VAI], Triglyceride-Glucose [TyG] Index) was compared between groups. Results: Within PCOS, atherogenic lipid indices were similar in obese versus non-obese subgroups. Non-obese PCOS demonstrated significantly higher atherogenic lipid and IR indices compared to controls (all P<0.05). Receiver operating characteristic (ROC) curve analysis identified LAP (Area under the curve [AUC] =0.747, 95% confidence intervals [CI]: 0.647-0.844, threshold=18.05), VAI (AUC=0.707, 95% CI: 0.605-0.811, threshold=1.15), and TyG (AUC=0.701, 95% CI: 0.583-0.814, threshold=8.29) as the three best indices distinguishing non-obese PCOS from healthy controls. Conclusions: Elevated atherogenic lipid and IR indices in non-obese PCOS compared to non-obese controls, alongside similar atherogenic markers between obese and non-obese PCOS groups are consistent with the notion that PCOS may independently contribute to atherogenesis beyond obesity-related mechanisms. In this exploratory analysis, data-driven thresholds for LAP, VAI and TyG were identified in non-obese PCOS. These values require external validation in larger, multi-center cohorts before they can be considered for routine CVD risk screening or monitoring.